Mitotic-Spindle Organizing Protein MztA Mediates Septation Signaling by Suppressing the Regulatory Subunit of Protein Phosphatase 2A-ParA in Aspergillus nidulans - Jiang, Ping; Zheng, Shujun; Lu, Ling (Frontiers in Microbiology, 2018)
Abstract The proper timing and positioning of cytokinesis/septation is crucial for hyphal growth and conidiation in Aspergillus nidulans. The septation initiation network (SIN) components are a conserved spindle pole body (SPB) localized signaling cascade and the terminal kinase complex SidB-MobA, which must localize on the SPB in this pathway to trigger septation/cytokinesis. The regulatory subunit of phosphatase PP2A-ParA has been identified to be a negative regulator capable of inactivating the SIN. However, little is known about how ParA regulates the SIN pathway and whether ParA regulates the septum formation process through affecting the SPB-localized SIN proteins. In this study, through RNA-Seq and genetic approaches, we identified a new positive septation regulator, a putative mitotic-spindle organizing protein and a yeast Mzt1 homolog MztA, which acts antagonistically towards PP2A-ParA to coordinately regulate the SPB-localized SIN proteins SidB-MobA during septation. These findings imply that regulators, phosphatase PP2A-ParA and MztA counteract the septation function probably through balancing the polymerization and depolymerization of microtubules at the SPB.